HEALTH COMMUNICATION STRATEGIES IN ACCELERATING THE REDUCTION OF STUNTING CONDITIONS IN TELUK TAMBA VILLAGE, BARITO KUALA, KALIMANTAN SELATAN - Noviana Sari (Universitas Lambung Mangkurat, 2023)
Health Communication plays an important role in the success of programs and policies implemented by the government. The rise of health conditions in the community, especially the stunting condition, which is worrying at this time, is a program that is carried out and implemented by the government to reduce the level of stunting conditions, especially in children. Considering that stunting is a government program that must be implemented by all health offices without exception. Therefore, to reduce stunting, the government, especially the puskesmas, must take part in this program so that it can reduce stunting. The purpose of this study was to find out the health communication strategy implemented by the puskesmas for the community, and how successful the program's policies were in reducing stunting rates. The research method used is a qualitative descriptive approach. The data collection techniques used in this study were in two ways, namely in-depth interviews, and documentation through observation with informants from the Head of Teluk Tamba Village, the Chairperson of the PKK in Teluk Tamba Village, and 6 parents of toddlers who experienced stunting. Data analysis techniques with observation and interviews. The results of the study show that the role of the puskesmas is very much needed for the success of the program's policies and that health communication between the puskesmas and the community runs very well and smoothly.